Potensi Aktivitas Antibakteri Antara Ekstrak dan Fraksi Kulit Jeruk Terhadap Ulkus Diabetes - Farren Farren; Rena Meutia; Astriani Natalia Br Ginting; Asyrun Alkhairi Lubis (Universitas Muhammadiyah Manado, 2025)
Diabetic ulcers, a chronic complication of diabetes mellitus, result from long-term uncontrolled blood sugar levels and are characterised by infection-prone foot wounds. Staphylococcus aureus is often found as the bacteria that cause infection in these wounds. Antibiotic resistance has become a serious challenge in medicine, so alternatives such as orange peel (Citrus sinensis (L.) Osbeck) were investigated for their metabolite content with antibacterial potential. This study was designed experimentally with a Posttest Only Control Group Design approach. Orange peels were processed through sorting, drying, extraction using 96% ethanol, and fractionation with ethyl acetate. Antibacterial activity test was conducted by disc method against Staphylococcus aureus, using ethanol extract and ethyl acetate fraction. DMSO and mupirocin were used as negative and positive controls, with concentrations of 25%, 50%, and 75%. The results showed that the ethanol extract had antibacterial activity, with a concentration of 75% producing the largest inhibition zone (13.56 mm), including the medium category. However, the ethyl acetate fraction did not show antibacterial activity at all concentrations, presumably due to the low levels of extractable semipolar metabolites. Environmental factors such as UV light, humidity, and high temperature during drying are also thought to affect metabolite levels. It was concluded that ethanol extract of orange peel was more effective than ethyl acetate fraction in inhibiting the growth of Staphylococcus aureus.